Anti-fingerprint coating for touch screen and synthesis method of anti-fingerprint coating
By using fluorine-containing copolymers, reversible crosslinking agents and multi-component solvents, the problem of insufficient chemical resistance of existing coatings is solved, and efficient anti-fingerprint and optical clarity effects are achieved, which is suitable for environments with high humidity and frequent disinfection.
Patent Information
- Application Number
- CN202510356872.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-25
AI Technical Summary
The existing anti-fingerprint coatings are insufficient in the face of frequent use of alcohol and other disinfectants, resulting in reduced anti-fingerprint effect and weakened optical clarity.
The synthesis method of fluorine-containing copolymer, reversible crosslinking agent and multi-component solvent is adopted to form a stable crosslinking network by evaporating and introducing water vapor in stages, thereby improving the mechanical strength and durability of the coating.
The anti-fingerprint performance and optical clarity of the coating are significantly improved, ensuring excellent performance in a high humidity and frequent disinfection environment for a long time.
Smart Images

Figure CN119875443A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of touch screens, and in particular relates to an anti-fingerprint coating for a touch screen and a synthesis method thereof. Background Art
[0002] In the current technological environment, touch screen devices have been widely used in many fields. For example, in hospitals and clinics, touch screens are widely used in various medical devices, such as patient monitors, electronic medical record systems, operating room equipment control panels, etc. These devices require highly reliable operating interfaces to ensure that medical staff can quickly and accurately input and obtain information.
[0003] Medical staff frequently touch and operate the touch screen, which easily leaves fingerprints and grease on the screen surface. This not only affects the aesthetics of the touch screen, but may also hinder the normal use of the touch function. In order to prevent cross infection, the touch screen of medical equipment also needs to be disinfected frequently, usually with an alcohol-containing disinfectant. Disinfectants such as alcohol will corrode the surface coating of the touch screen, causing the coating to age, fall off or degrade, resulting in impaired anti-fingerprint effect and transparency. In addition, frequent chemical cleaning is accompanied by high humidity, which will have an adverse effect on the materials and coatings of the touch screen, resulting in a decrease in coating performance, such as weakened anti-fingerprint ability, water stains on the coating surface, and other problems, which in turn affects the transparency and operational sensitivity of the touch screen.
[0004] Existing anti-fingerprint coatings often lack chemical resistance and are easily corroded when frequently used with disinfectants such as alcohol, resulting in reduced anti-fingerprint effects and weakened optical clarity. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide an anti-fingerprint coating for a touch screen and a synthesis method thereof, aiming to solve the problems of reduced anti-fingerprint effect of the coating and weakened optical clarity.
[0006] In order to solve the above problems, the present invention provides a method for synthesizing an anti-fingerprint coating for a touch screen, the steps comprising: S1. Mixing a fluorinated copolymer, a reversible crosslinking agent and a multi-component solvent to obtain a coating mixed solution, wherein the multi-component solvent includes a fast-evaporating plasticizer, a slow-evaporating plasticizer and a polar solvent; S2, coating the coating mixed solution on the touch screen, heating after coating to evaporate the fast-volatile plasticizer, and introducing water vapor after evaporation; S3, after stopping the introduction of water vapor, the temperature is raised again to evaporate the slow-evaporating plasticizer, and after the evaporation is completed, light curing is performed to obtain an anti-fingerprint coating for a touch screen.
[0007] In some embodiments, step S1 includes: S1.1, placing the fluorinated copolymer and the reversible crosslinking agent in a stirring reaction vessel, stirring at a speed of 100-200 rpm, a stirring temperature of 30-35°C, and an ambient humidity of 8-10%; S1.2, add fast-evaporating plasticizer, increase the stirring speed to 200-300 rpm, reduce the ambient pressure to 0.9-0.95 atm, and continue stirring for 3-5 minutes after the addition is completed; S1.3. Add slow-evaporating plasticizer, reduce the stirring speed to 100-150 rpm, increase the stirring speed to 150-200 rpm after the addition is complete, add polar solvent, continue stirring for 10-15 minutes after the addition is complete, and obtain a coating mixed solution.
[0008] In some embodiments, in the multi-component solvent, calculated by weight percentage, the slow-evaporating plasticizer accounts for 30-50%, the polar solvent accounts for 10-20%, and the balance is the fast-evaporating plasticizer.
[0009] In some embodiments, step S2 includes: S2.1. Place the touch screen in a spraying station of a spraying device, and then spray the coating mixed solution on the touch screen, wherein the spraying device is provided with a nozzle, a circulating fan, a heating unit and a sensor unit, the atomization frequency of the nozzle is 100-200 kHz, and the spraying time is 1-2 min; S2.2. After spraying, the coating is heated to 50-60°C. A circulating fan is turned on to blow the coating mixed solution on the touch screen at a horizontal airflow speed of 0.5-1 m / s. When the evaporation of the fast-volatile plasticizer is detected, water vapor is introduced for 3-5 minutes to raise the ambient humidity to 25-30%.
[0010] In some embodiments, the step of detecting that the evaporation of the fast-volatile plasticizer is complete includes: detecting that the viscosity of the coating mixed solution reaches a preset viscosity value, detecting that the mass of the coating mixed solution decreases to within a preset mass range, and detecting that a characteristic absorption peak in the spectrum of the coating mixed solution drops to at least one of a preset threshold value.
[0011] In some embodiments, step S3 includes: S3.1. Stop introducing water vapor and adjust the horizontal airflow speed to 0.2~0.5m / s until the ambient humidity reaches 15~20%; S3.2, raising the heating temperature to 90-100° C. for 5-10 min, detecting that the slow-evaporating plasticizer has been evaporated, irradiating the coating mixed solution with ultraviolet light to obtain an anti-fingerprint coating for a touch screen.
[0012] In some embodiments, the step of detecting that the evaporation of the slow-evaporating plasticizer is completed includes: detecting that the acoustic parameter of the coating mixed solution reaches a preset curing reference value, detecting that the optical transmittance change amplitude of the coating mixed solution reaches a preset light transmittance amplitude range, and detecting that the thickness change amplitude of the coating mixed solution reaches at least one of a preset thickness amplitude range.
[0013] The present invention also provides an anti-fingerprint coating for a touch screen, which is made by the synthesis method of the anti-fingerprint coating for a touch screen as described above, wherein the anti-fingerprint coating for a touch screen comprises a fluorine-containing copolymer, a reversible crosslinking agent and a multi-component solvent, wherein the fluorine-containing copolymer comprises at least one of polytetrafluoroethylene, polyvinylidene fluoride and fluorinated ethylene propylene copolymer, the reversible crosslinking agent comprises at least one of bismaleimide-fulvene dimer, bisthioethyl ether and adipaldehyde, the multi-component solvent comprises a fast-evaporating plasticizer, a slow-evaporating plasticizer and a polar solvent, the fast-evaporating plasticizer comprises at least one of acetone, ethyl acetate and methyl ethyl ketone, the slow-evaporating plasticizer comprises at least one of butyl butyrate, dipropylene glycol methyl ether and cyclohexanone, and the polar solvent comprises at least one of ethanol, methanol and propylene glycol.
[0014] Compared with the prior art, the anti-fingerprint coating for touch screen and the synthesis method thereof in the present invention have the following beneficial effects: Fluorinated copolymers and reversible crosslinkers provide excellent anti-fingerprint performance and chemical resistance, and the multi-component solvent system ensures uniformity and high transparency of the coating. Phased evaporation and introduction of water vapor allow sufficient time for the molecules inside the coating to rearrange and crosslink, enhancing the anti-fingerprint effect of the coating in high humidity environments. UV curing forms a stable crosslinking network, improving the mechanical strength and durability of the coating, ensuring long-term high transparency and anti-fingerprint performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The figure is a schematic flow chart of a method for synthesizing an anti-fingerprint coating for a touch screen in one embodiment of the present invention. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0017] Please refer to Figure 1 The present invention provides a method for synthesizing an anti-fingerprint coating for a touch screen, the steps comprising: S1. Mixing a fluorine-containing copolymer, a reversible crosslinking agent and a multi-component solvent to obtain a coating mixed solution, wherein the multi-component solvent includes a fast-evaporating plasticizer, a slow-evaporating plasticizer and a polar solvent.
[0018] In the coating mixed solution, calculated by mass percentage, the fluorinated copolymer accounts for 20-40%, such as 20%, 30%, and 40%, the reversible crosslinker accounts for 1-5%, such as 1%, 3%, and 5%, and the remainder is a multi-component solvent.
[0019] In the multi-component solvent, calculated by mass percentage, the slow-evaporating plasticizer accounts for 30-50%, such as 30%, 40%, and 50%, the polar solvent accounts for 10-20%, such as 10%, 15%, and 20%, and the balance is the fast-evaporating plasticizer.
[0020] The fluorine-containing copolymer includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, and fluorinated ethylene propylene copolymer, the reversible crosslinking agent includes at least one of bismaleimide-fulvene dimer, bisthioethyl ether, and adipaldehyde, the fast-evaporating plasticizer includes at least one of acetone, ethyl acetate, and methyl ethyl ketone, the slow-evaporating plasticizer includes at least one of butyl butyrate, dipropylene glycol methyl ether, and cyclohexanone, and the polar solvent includes at least one of ethanol, methanol, and propylene glycol.
[0021] Fluorinated copolymers: polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), fluorinated ethylene propylene copolymer (FEP) These fluorinated polymers are extremely hydrophobic and can significantly reduce the adhesion of water and grease (such as fingerprints) to the coating. PTFE in particular has super non-stickiness and is widely used in applications that require low friction and low adhesion. Fluorinated polymers excel in chemical stability and can resist the erosion of the coating by a variety of solvents and disinfectants (such as alcohol and disinfectants), ensuring that the coating is not damaged or degraded during frequent wiping and disinfection. Due to its high transparency, fluorinated polymers contribute to the optical clarity of the coating, avoid discoloration or blurring of the coating, thereby ensuring the display effect of the touch screen, improving the anti-fingerprint and anti-fouling properties of the coating, and extending the service life of the coating. In medical applications, it has the function of being resistant to disinfection and can withstand frequent cleaning and alcohol wiping.
[0022] Reversible crosslinkers: bismaleimide-fulvene dimer, bisthioethyl ether, adipaldehyde, etc., improve the mechanical strength and durability of the coating. Reversible crosslinkers form a three-dimensional network structure of the coating through crosslinking, enhancing the hardness, strength and wear resistance of the coating. These crosslinkers can make the coating have reversible structural changes when the humidity changes, enhance the elasticity and adaptability of the coating, and ensure that the coating maintains good performance in a humid environment. Reversible crosslinkers can also improve the anti-aging properties of the coating and prevent the coating from cracking or fading after long-term use. Provide the coating with wear resistance and high durability, so that the coating can maintain its function during repeated wiping and disinfection. By providing reversible crosslinking function, the coating can respond to high humidity environments, achieve the property of "humidity-sensitive elasticity", and reduce the adsorption of fingerprint grease.
[0023] "Humidity-sensitive elasticity" is a material property that refers to the ability of a material to exhibit adjustable elasticity and flexibility under different humidity environments. This property is particularly important in medical environments with high humidity and frequent disinfection, and is particularly suitable for anti-fingerprint coatings for touch screens.
[0024] The realization of humidity-sensitive elasticity depends on the design of the molecular structure and chemical composition inside the material. In a high humidity environment, the hydrophilic groups in the material (such as hydroxyl, amine, carboxyl, etc.) will absorb water molecules in the environment. The adsorption of water molecules causes the distance between polymer chains to increase, and the microstructure of the material expands, which is manifested as an increase in elasticity and flexibility. Reversible crosslinkers (such as bismaleimide-fulvene dimer, bisthioethyl ether, adipaldehyde, etc.) are introduced into the material. These crosslinkers can undergo reversible reactions under specific conditions (such as temperature and humidity). When the ambient humidity increases, the crosslinking network partially dissociates, making the polymer chain more flexible; when the humidity decreases, the crosslinking network reforms and restores the stability of the material. The slow-evaporating plasticizers (such as butyl butyrate, dipropylene glycol methyl ether, cyclohexanone, etc.) added to the material adjust the flexibility and elasticity of the material at different humidity. These plasticizers can absorb water under high humidity conditions, further promoting the swelling and softness of the material. The swelling caused by humidity changes not only occurs at the level of the polymer chain, but also manifests itself in the microstructure of the coating surface. Fine-tuning of the surface microstructure helps reduce the adhesion of fingerprint oil and moisture, improving the anti-fingerprint effect.
[0025] Fast-evaporating plasticizers: acetone, ethyl acetate, methyl ethyl ketone, promote the initial drying of the coating: these fast-evaporating plasticizers evaporate quickly, which can accelerate the drying process of the coating and avoid irregular bubbles or sagging on the coating surface. Fast-evaporating plasticizers help improve the leveling of the coating, so that the coating can be evenly distributed on the touch screen surface after coating, forming a smooth and consistent film. It increases the initial curing speed of the coating, thereby improving production efficiency, and can ensure the smoothness and uniformity of the coating during the coating process to avoid coating defects.
[0026] Slow-evaporation plasticizers can extend the drying time of the coating and prevent the coating from curing prematurely, thereby ensuring that the coating maintains good flexibility and elasticity during the film-forming process. Slow-evaporation plasticizers help the coating form a stable molecular structure during the curing process, increase the adhesion between the coating and the touch screen surface, and ensure that the coating is firmly attached to the screen surface. In the final curing stage of the coating, the timely evaporation of the slow-evaporation plasticizer helps the coating maintain a certain degree of flexibility and pressure resistance, enabling the coating to adapt to changes in humidity. By appropriately extending the evaporation time, the flexibility and durability of the coating are enhanced, and the coating is prevented from cracking.
[0027] Polar solvents can interact with other ingredients in the coating (such as fluorinated copolymers and reversible cross-linkers) to enhance the adhesion of the coating to the touch screen surface, ensuring that the coating is evenly distributed and firmly adhered. Polar solvents help dissolve and mix other coating ingredients, ensure the uniformity and stability of the coating formula, improve the adhesion and uniformity of the coating, ensure that the coating does not fall off or bubble during use, ensure the transparency of the coating, and do not affect the display effect of the touch screen.
[0028] Through the precise ratio and synergistic effect of these five components, the coating on the touch screen can achieve anti-fingerprint performance, high transparency and optical properties, humidity adaptability and elasticity, chemical resistance and disinfection resistance, and controllability and efficiency of the film-forming process.
[0029] In one embodiment, step S1 includes: S1.1. Place the fluorinated copolymer and the reversible crosslinking agent in a stirring reaction vessel and stir them. The stirring speed is 100-200 rpm, for example, 100 rpm, 150 rpm, 200 rpm. The stirring temperature is 30-35°C, for example, 30°C, 32°C, 35°C. The ambient humidity is 8-10%, for example, 8%, 9%, 10%.
[0030] Step S1.1 ensures the uniformity, stability and high quality of the coating mixed solution by mixing the fluorinated copolymer and the reversible cross-linking agent under specific stirring speed, temperature and low humidity conditions. The setting of these specific operating parameters not only promotes the full dissolution and uniform dispersion of each component, but also effectively controls the reaction rate and solvent volatilization, avoiding the occurrence of coating defects. Ultimately, the obtained coating mixed solution has excellent anti-fingerprint performance, high transparency, chemical resistance and durability, laying a solid foundation for subsequent coating, curing and other process steps, ensuring that the final anti-fingerprint coating exhibits excellent technical performance in a medical environment with high humidity and frequent disinfection.
[0031] S1.2, add fast-evaporating plasticizer, increase the stirring speed to 200-300 rpm, for example, 200 rpm, 250 rpm, 300 rpm, reduce the ambient pressure to 0.9-0.95 atm, for example, 0.9 atm, 0.92 atm, 0.95 atm, continue stirring for 3-5 min after adding, for example, 3 min, 4 min, 5 min.
[0032] By combining high stirring speed with low ambient pressure, the uniform dispersion of fast-evaporating plasticizers in the coating mixed solution is ensured, avoiding the problems of uneven dissolution of solvents and local concentrations that are too high or too low. Low ambient pressure allows fast-evaporating plasticizers to evaporate quickly at lower temperatures, reducing residues and improving coating quality. The uniform coating, enhanced adhesion and anti-fingerprint effects enable the touch screen to maintain high transparency and anti-fingerprint functions for a long time in medical scenarios, improving the user experience. By increasing the stirring speed and appropriately extending the stirring time, each component is ensured to be fully mixed, providing a more stable and uniform solution for subsequent steps, which helps to improve production efficiency and product consistency.
[0033] S1.3, add slow-evaporating plasticizer, reduce the stirring speed to 100-150rpm, for example, it can be 100rpm, 130rpm, 150rpm, after adding, increase the stirring speed to 150-200rpm, for example, it can be 150rpm, 180rpm, 200rpm, add polar solvent, after adding, continue stirring for 10-15min, for example, it can be 10min, 13min, 15min, to obtain a coating mixed solution.
[0034] After adding the slow-evaporating plasticizer, reduce the stirring speed to 100~150rpm to avoid excessive stirring that may cause bubbles in the coating solution or uneven dispersion of components. Slow stirring helps the slow-evaporating plasticizer to gradually and evenly distribute in the coating mixed solution, avoiding unnecessary damage caused by violent disturbance of the solution.
[0035] Increasing the stirring speed to 150~200rpm helps to enhance the collision and mixing between the components in the solution and improve the uniformity of the coating solution. At this point, after the slow-evaporating plasticizer has been added, the viscosity of the solution is moderate, and the higher stirring speed can help the polar solvent to be evenly dispersed in the coating solution, ensuring the stability and consistency of the solution. At a high stirring speed, the polar solvent can quickly disperse and form a uniform solution with the slow-evaporating plasticizer to avoid component stratification.
[0036] After adding the slow-evaporating plasticizer and polar solvent, prolonging the stirring time to 10~15min will help to fully mix the components and avoid the occurrence of local uneven components. Prolonging the stirring time ensures that the slow-evaporating plasticizer is completely integrated with other solvents, improving the uniformity and stability of the coating. Long-term stirring allows the solution to maintain good stability at high stirring speeds, reduces solvent stratification or local unevenness, and enables the coating to be evenly coated on the touch screen surface, improving the coating quality and adhesion. Through moderate stirring, the slow-evaporating plasticizer can form a stronger adhesion with the substrate surface, making the coating less likely to fall off when subjected to external forces (such as cleaning or wiping). In addition, the flexibility of the coating is also improved to adapt to environmental conditions such as high humidity and frequent cleaning, ensuring a long-lasting anti-fingerprint effect.
[0037] Ultimately, S1.3 not only ensures the uniformity of the coating mixed solution through a reasonable stirring speed, time, and solvent addition order, but also improves the functionality of the coating, ensuring that the touch screen can maintain excellent anti-fingerprint effects and optical clarity for a long time in a medical environment with high humidity and frequent cleaning.
[0038] In one embodiment, step S1 also includes S1.4, adding self-healing particles to the coating mixed solution, the self-healing particles including a photocurable monomer and a polymer shell encapsulating the photocurable monomer, wherein the polymer shell includes at least one of hexamethylene diisocyanate, polyethylene glycol, and trimethylolpropane, and the photocurable monomer includes at least one of oxyacrylate, trimethylolpropane triacrylate, butyl acrylate, hexamethylene glycol diacrylate, polyurethane acrylate, epoxy resin modified acrylate, aliphatic polyurethane acrylate, and methyl methacrylate.
[0039] The steps to make self-healing particles are as follows: Dissolve the photocurable monomer in an appropriate amount of oil phase solvent, stir evenly to form a core solution, add the core solution dropwise into the water phase, disperse at a speed of 1000-2000 rpm for 10-15 minutes to form an oil-in-water emulsion.
[0040] Add the oil-in-water emulsion dropwise into another aqueous phase, reduce the stirring speed to 500-1000 rpm, and continue stirring for 10-20 min to form a water-oil-water emulsion.
[0041] Add the polymer shell raw material to the water-oil-water emulsion, maintain stirring at 30-50°C for 30-60 minutes until the polymer shell is fully formed, and control the pH at 6-8 to optimize the cross-linking efficiency.
[0042] The particles are separated by a separatory funnel or filtered out by a filter membrane, and the self-repairing particles are repeatedly washed with deionized water to remove unreacted products and solvents. The self-repairing particles are placed in a vacuum drying oven and dried at 40-50°C for 12-24 hours.
[0043] The oil phase solvent includes at least one of dichloromethane and cyclohexane, the water phase solvent includes deionized water and a surfactant, and the surfactant includes at least one of polyethylene glycol and polyvinyl pyrrolidone.
[0044] When the coating is scratched or damaged by external forces, it can automatically trigger the self-repairing particles to release photocurable monomers and quickly repair surface defects through ultraviolet light irradiation. The introduction of self-repairing particles enables the coating to have dynamic repair capabilities, effectively extending the service life of the coating, especially in medical environments with frequent wiping and disinfection to maintain long-term stable performance. The self-repairing function can continuously repair the microstructure of the coating surface, ensuring the stability and durability of the anti-fingerprint performance and avoiding performance degradation due to local damage.
[0045] S2. Applying the coating mixed solution on the touch screen, heating after the coating is completed to evaporate the fast-volatile plasticizer, and introducing water vapor after the evaporation is completed.
[0046] As the fast-evaporating plasticizer evaporates quickly, local voids are formed inside the coating, laying the foundation for the subsequent water vapor diffusion and "humidity-sensitive elastic" structure. The formation of the initial micro / nanopore structure helps the coating to further evolve into a functional microstructure under subsequent humidity control.
[0047] The introduction of water vapor causes the water molecules inside the coating to diffuse into the initially formed pores, forming a more regular micro / nanopore structure. Under the penetration and condensation of water molecules, the micro / nanopores further expand and form a uniform and stable pore distribution on the coating surface. During the introduction of water vapor, the microstructure of the coating surface is adjusted, the surface energy gradually decreases, and a low surface energy hydrophobic surface is formed, which improves the anti-fingerprint performance of the coating, reduces the adhesion of grease and water, forms a denser and smoother coating surface, and enhances the optical transparency and display clarity of the coating.
[0048] Step S2 includes: S2.1. Place the touch screen in a spraying station of a spraying device, and then spray the coating mixed solution on the touch screen, wherein the spraying device is provided with a nozzle, a circulating fan, a heating unit and a sensor unit, the atomization frequency of the nozzle is 100-200kHz, for example, it can be 100kHz, 150kHz, 200kHz, and the spraying time is 1-2min, for example, it can be 1min, 1.5min, 2min.
[0049] The high atomization frequency of the nozzle can convert the coating mixed solution into uniform and tiny droplets (the droplet diameter can be 10~50μm). The coating droplets are more uniform, avoiding the aggregation and sagging of large droplets, improving the coverage and uniformity of the coating on the touch screen surface, and ensuring that the coating surface is flat and smooth. High-frequency atomization makes the solution distribution in the spraying process more controllable, the amount of liquid sprayed is small and the distribution is fine, achieving precise control of the coating thickness, avoiding the problem of too thick or too thin thickness, and ensuring subsequent optical transparency and anti-fingerprint performance.
[0050] The droplet size is small and evenly distributed, which helps to reduce bubbles or particles remaining inside the coating during the spraying process, further improving the optical performance of the coating, increasing the light transmittance of the coating and maintaining the display clarity of the touch screen.
[0051] The controllable range of spraying time can be adjusted according to the size of the touch screen and the fluidity of the coating solution. Ensure that the coating can evenly cover the touch screen surface without dry spraying or overspraying. Optimization of spraying time ensures that the coating thickness of each part is consistent, whether it is the edge area or the center area, and can be evenly covered. Avoid uneven thickness of the coating and improve the optical performance and mechanical strength of the coating.
[0052] The circulation fan generates horizontal airflow to evenly disperse the coating droplets on the touch screen surface to avoid excessive accumulation of the coating. In other embodiments, the circulation fan can provide airflow alternating between horizontal and vertical directions, and the switching cycle can be controlled within 1 to 2 minutes. The alternating action of vertical and horizontal airflow introduces a dynamic diffusion force field, which further reduces the surface energy of the coating, improves the uniformity of coating coverage, and avoids excessive accumulation of droplets in local areas causing sagging.
[0053] The airflow of the circulation fan can accelerate the evaporation process of fast-volatile plasticizers, quickly form a preliminary solidified coating, and avoid long-term retention of solvents that affect coating performance.
[0054] The heating unit can reduce the viscosity of the coating solution and promote the expansion and leveling of the droplets on the touch screen surface. It can improve the surface smoothness of the coating and form a flat and uniform film structure. It can avoid the droplets solidifying too quickly due to low temperature, resulting in surface graininess or poor leveling. The temperature provided by the heating unit helps to accelerate the volatilization of fast-evaporating plasticizers and form a more stable coating structure. It dries quickly, improves production efficiency, and lays the foundation for subsequent water vapor treatment.
[0055] The sensor unit can monitor the temperature, humidity and droplet distribution of the coating in real time during the spraying process. The spraying conditions are adjusted through feedback control to ensure uniform coating thickness and distribution. The sensor monitors the spraying environment and equipment parameters to provide optimization data for subsequent heating and drying, improve spraying consistency, and reduce coating quality fluctuations.
[0056] S2.2. After spraying, heating is performed at a temperature of 50-60°C, such as 50°C, 55°C, or 60°C. The circulating fan is turned on to blow the coating mixed solution on the touch screen at a horizontal airflow speed of 0.5-1 m / s. When the evaporation of the fast-volatile plasticizer is detected, water vapor is introduced for 3-5 minutes, such as 3 minutes, 4 minutes, or 5 minutes, so that the ambient humidity rises to 25-30%, such as 25%, 28%, or 30%.
[0057] The heating temperature is close to the boiling point range of the fast-volatile plasticizer, which can significantly increase its evaporation rate. The volatile components in the coating solution are quickly reduced to form a uniform and dense preliminary coating structure. The residual volatile components can avoid fluctuations in coating performance, providing a stable basis for subsequent processing. Heating reduces the viscosity of the coating solution, allowing it to flow more fully on the touch screen surface. The surface smoothness of the coating is improved, the surface granularity or ripples are avoided, and the optical transparency and aesthetics of the touch screen are improved.
[0058] After the water vapor is introduced, the ambient humidity rises rapidly to 25-30%, and the hydrophilic groups (such as polar functional groups) in the coating absorb water, resulting in a micro-swelling effect. The "humidity-sensitive elastic" property of the coating surface is initially formed, providing a functional basis for the final anti-fingerprint performance. It promotes the formation of microscopic pore structure on the coating surface and further optimizes the anti-fingerprint performance of the coating. Water vapor can penetrate into the internal structure of the coating, interact with polar components, and improve the fluidity of the molecular chain. It causes a micro-rearrangement of the molecular chain of the coating, which is conducive to the formation of a stable cross-linked network in the subsequent curing process.
[0059] The step of detecting that the evaporation of the fast-volatile plasticizer is complete includes: detecting that the viscosity of the coating mixed solution reaches a preset viscosity value, detecting that the mass of the coating mixed solution decreases to a preset mass range, and detecting that a characteristic absorption peak in the spectrum of the coating mixed solution drops to at least one of a preset threshold value.
[0060] By accurately detecting the evaporation degree of fast-evaporating plasticizers, the coating formation process is ensured to be uniform and consistent, avoiding uneven thickness or surface defects caused by solvent residues, improving the optical transparency and uniformity of the coating, and avoiding bubbles, holes or solvent retention in the coating due to the residue of fast-evaporating components. After the fast-evaporating plasticizer is completely evaporated, the initial curing of the coating is completed, providing ideal conditions for subsequent water vapor treatment and final curing. Provide a stable coating substrate to ensure the formation of moisture-sensitive pore structures and improve functionality. Accurately determine the time when volatilization is completed to avoid overheating or extended drying time, saving energy and production time.
[0061] The online viscometer monitors the viscosity of the coating mixed solution in real time. When the viscosity reaches the preset threshold (such as the minimum viscosity required for coating leveling), it is considered that the volatilization is complete. It is suitable for real-time monitoring of dynamic coating processes and can be combined with automatic control systems for feedback adjustment. The evaporation of fast-evaporating plasticizers will cause the viscosity of the coating solution to gradually increase. When the solvent is completely evaporated, the coating viscosity reaches a stable value. At this time, the online viscosity test can be used to determine whether the volatilization is complete. The presence of fast-evaporating plasticizers reduces the cohesion of the coating solution, and its evaporation process will gradually increase the flow resistance (i.e. viscosity) of the solution.
[0062] The mass change of the coating mixed solution before and after spraying and during the heating process is monitored in real time by an electronic balance or an online mass sensor. When the mass drops to a preset range (such as the remaining coating weight after the mass of the fast-volatile component is completely evaporated), it is judged to be complete. It is used to detect mass changes during the solvent evaporation process in the laboratory or production line. The mass of the fast-volatile plasticizer gradually decreases during the evaporation process. When the mass of the mixed solution drops to a preset range (such as only the slow-volatile component, polar solvent and solid component are left), it can be judged that the solvent has been completely evaporated. The initial mass of each component in the coating mixed solution is known, and the degree of removal of the fast-volatile component is determined by monitoring the mass change and comparing it with the preset target mass.
[0063] Fourier transform infrared spectrometer (FTIR) or ultraviolet-visible spectrometer (UV-Vis) is used to detect the characteristic absorption peak of fast-volatile plasticizers in the coating mixed solution (such as the characteristic absorption peak of C=O stretching vibration of acetone, with a wave number of about 1720cm⁻¹). When the characteristic peak drops below the preset threshold, it is judged that the volatilization is complete. It is suitable for detection scenarios where the solvent type in the coating is clear and the absorption characteristics are obvious. Fast-volatile plasticizers have specific spectral absorption peaks (such as the C=O characteristic absorption peak in the infrared spectrum). During the evaporation of the solvent, the intensity of its absorption peak gradually weakens. When the peak intensity drops below a certain threshold, it can be judged that the volatilization is complete. The molecules of each solvent have specific vibration modes and absorption spectra. Infrared or ultraviolet-visible spectra can quantitatively analyze the intensity changes of these absorption characteristics. For example, the C=O stretching vibration absorption of acetone is at 1720cm⁻¹. The decrease in its absorption intensity can be monitored in real time by FTIR with high precision, which can be used for the analysis of various solvent types or mixed solvent systems.
[0064] The above-mentioned preset judgment viscosity value, preset mass range, and preset threshold value can be obtained by repeated experiments, and a large number of test experiments with the same steps and formulas are performed to summarize the corresponding judgment values.
[0065] For the holes formed as the fast-evaporating plasticizer evaporates in step S2, the following calculation formula is used: in, represents the total driving force required for pore expansion, driven by the coating-solvent interfacial tension and the surface tension pressure of the pores Joint decision, It is the interfacial tension between fluoropolymer and water, which can be measured by a surface tension meter. As the humidity increases, the amount of water molecules adsorbed on the coating surface increases. will decrease, is the interfacial tension between fluorinated polymer and fast-evaporating plasticizer, which can be derived by droplet contact angle measurement instrument. and The values are constantly changing during the stirring process. The dynamic interfacial tension meter can measure the specific values. is the surface tension of a known fast-evaporating plasticizer, for example, the surface tension of acetone is 23.7 mN / m, is the contact angle between the coating and the fast-evaporating plasticizer, r is the current radius of the hole, is the surface tension between water and air, and its known value is 72.8mN / m.
[0066] The above equation is used to guide how to control the driving force of pore expansion during the evaporation of fast-volatile plasticizers. When it is too large, it will cause the holes to rupture or expand excessively, and volatilize too quickly, causing the coating to collapse or become defective, the light transmittance to decrease, atomization to occur, the surface to crack easily, and the wear resistance to decrease. If the temperature is too small, the pores will be too small, the humidity responsiveness and anti-fingerprint effect will decrease, and slow evaporation will lead to solvent residue.
[0067] Combining and derivatizing the above equations, we get ,when = 0, we can find the equilibrium radius where the driving force reaches its maximum value , , when the humidity conditions are controlled, the ambient humidity affects the vapor pressure distribution on the coating surface, thereby affecting the expansion rate and stability of the pores. Higher humidity reduces , thereby increasing the radius r of the pore. The introduction of water vapor increases the ambient humidity to 25%~30%, promoting the formation and expansion of the pores, and the cessation of water vapor reduces the ambient humidity to 15%~20%, stabilizing the pore structure.
[0068] Adjust the air flow speed. The air flow can assist the solvent volatilization through shear force, affecting the interfacial tension between the fluorinated polymer and the fast-evaporating plasticizer. , increase the air flow speed (such as 0.5~1m / s), because the solvent quickly leaves the coating surface, the surface tension is controlled to change rapidly, the fluorinated polymer is enriched on the coating surface, the surface energy decreases, and the interfacial tension with the fast-evaporating plasticizer is increased. Increase, thereby increasing r, accelerating pore expansion and solvent release. Reduce the air flow velocity (such as <0.2m / s), when the solvent evaporation rate slows down, the fast-evaporating plasticizer on the coating surface is not easy to evaporate completely, and the coating surface is still rich in solvent, which will make the molecular mobility of the coating surface higher, the enrichment rate of fluoropolymers slows down, and the surface tension changes lag to inhibit excessive expansion. Reduce, r decreases, and stabilizes the hole morphology.
[0069] S3, after stopping the introduction of water vapor, the temperature is raised again to evaporate the slow-evaporating plasticizer, and after the evaporation is completed, light curing is performed, and after the curing is completed, an anti-fingerprint coating for a touch screen is obtained.
[0070] The S3 step is the key link in the formation of the coating. After stopping the water vapor treatment, the temperature is raised to evaporate the slow-volatile plasticizer, and then light curing is performed to finally form a smooth, dense and highly functional coating.
[0071] Step S3 includes: S3.1. Stop introducing water vapor and adjust the wind speed of the horizontal airflow to 0.2-0.5 m / s, for example, 0.2 m / s, 0.3 m / s, 0.5 m / s, until the ambient humidity reaches 15-20%.
[0072] After the water vapor is stopped, the ambient humidity gradually returns to a lower range. At this time, the wetting properties of the coating surface are fixed, avoiding the collapse or instability of the surface micropore structure due to excessive wetting, ensuring that a regular micro / nano pore structure is formed on the coating surface, giving the coating humidity-sensitive elastic properties. Stabilizing the size and distribution of micropores is conducive to improving anti-fingerprint performance and surface smoothness.
[0073] After the water vapor is stopped, the remaining water in the coating evaporates naturally, thereby reducing the interference of water molecules on the coating curing reaction. Reducing the residual water inside the coating improves the integrity and uniformity of the cross-linking network during the subsequent curing process, and avoiding coating defects caused by residual water.
[0074] Adjust the wind speed of the horizontal airflow to a lower range to form a soft and uniform air flow, which can accelerate the evaporation of residual moisture in the coating without damaging the coating surface. Avoid uneven surface drying or coating film cracking caused by local high wind speed. Provide a stable evaporation environment to ensure the uniformity and surface smoothness of the coating. The airflow with a lower wind speed can effectively protect the coating surface and avoid the destruction of the coating surface structure or deformation of the microporous structure due to excessive airflow. Maintain the microscopic pore structure of the coating surface to ensure the stability of the anti-fingerprint characteristics and humidity response function.
[0075] S3.2. Raise the heating temperature to 90-100°C, such as 90°C, 95°C, or 100°C, and heat for 5-10 minutes, such as 5 minutes, 8 minutes, or 10 minutes. After detecting that the slow-volatile plasticizer has evaporated, irradiate the coating mixed solution with ultraviolet light to obtain an anti-fingerprint coating for a touch screen.
[0076] The slow-evaporating plasticizer has a higher boiling point and a slower evaporation rate. It can be further ensured to be completely volatilized and avoid residue in the coating by reducing the ambient pressure. For example, the ambient pressure can be reduced to 0.4~0.6atm, such as 0.4atm, 0.5atm, 0.6atm.
[0077] Increasing the temperature will reduce the viscosity of the polymer in the coating, allowing it to fully level on the surface, while eliminating the surface roughness or ripples caused by insufficient evaporation of the slow-evaporating plasticizer. The coating surface is smoother and the smoothness is significantly improved, avoiding the appearance of graininess or uneven thickness. It enhances the optical transparency and display clarity of the coating.
[0078] The residual of slow-evaporating solvent may interfere with the photocuring reaction, and its negative effects can be avoided by completely removing these residues by heating. Ensure the efficiency of the photocuring reaction, form a uniform cross-linking network, and improve the strength and durability of the coating.
[0079] UV irradiation stimulates the free radical polymerization reaction of the photocurable monomer through the initiator, and quickly forms a high-density three-dimensional cross-linked network. The curing time is short, which improves production efficiency. The surface hardness of the coating is significantly improved, forming excellent scratch resistance and wear resistance. The cross-linked network formed by photocuring has the characteristics of high strength and high density. The wear resistance and impact resistance of the coating are improved to adapt to the frequent use and cleaning needs of the touch screen. The flexibility of the coating is also improved, reducing cracking or shedding caused by external forces. During the photocuring process, the fluorinated copolymer chain segments tend to align to the surface of the coating to form a low surface energy interface. The adhesion of fingerprint grease is significantly reduced, and the anti-fingerprint performance is enhanced. The hydrophobicity and anti-fouling properties of the coating are improved, making it easy to clean.
[0080] UV curing eliminates light scattering caused by residual solvents or uneven structures inside the coating. The coating has excellent optical transparency, meeting the high requirements of touch screens for display clarity.
[0081] After the step of stopping the introduction of water vapor in step S3.1, the step also includes introducing an atmosphere containing carbon dioxide, that is, step S3.1 is changed to stopping the introduction of water vapor, introducing a carbon dioxide atmosphere and adjusting the wind speed of the horizontal airflow to 0.2~0.5m / s, and then stopping the introduction of the carbon dioxide atmosphere until the ambient humidity reaches 15~20%.
[0082] Through the diffusion of carbon dioxide gas, a weakly acidic microenvironment is formed on the surface of the coating, inducing the cross-linking phase change of the polymer chain. After the carbon dioxide gas stops, ultraviolet light curing is carried out to make the coating finally form a film, achieving a denser and more uniform microstructure on the coating surface, improving the hardness and humidity response performance of the coating, and optimizing the anti-fingerprint effect.
[0083] The step of detecting that the evaporation of the slow-volatile plasticizer is completed includes: detecting that the acoustic parameter of the coating mixed solution reaches a preset curing reference value, detecting that the optical transmittance change amplitude of the coating mixed solution reaches a preset light transmittance amplitude range, and detecting that the thickness change amplitude of the coating mixed solution reaches at least one of a preset thickness amplitude range.
[0084] By detecting the changes in key parameters of the coating solution during the evaporation of the slow-evaporating plasticizer, the solvent is ensured to be completely evaporated. Avoid surface defects caused by solvent residues, ensure that the coating surface is smooth and transparent, and meet the requirements of high-resolution display on the touch screen. Detect changes in coating thickness to ensure that the coating thickness is stable within the preset range after the slow-evaporating plasticizer is evaporated. Prevent the coating from being too thin or too thick, avoid the degradation of optical properties or poor anti-fingerprint performance due to uneven thickness, and provide a stable coating substrate for the subsequent photocuring stage. After the slow-evaporating plasticizer is completely evaporated, the molecular chains of the coating are rearranged and densified, thereby enhancing its mechanical properties and durability. The coating exhibits excellent wear resistance, scratch resistance and long-term stability, and is suitable for high-frequency cleaning and touch scenarios.
[0085] The acoustic parameters (such as sound velocity and acoustic impedance) of the coating mixture are closely related to its physical state. During the gradual evaporation of the slow-evaporating plasticizer, the density and elastic modulus of the coating change, thereby changing the propagation speed and acoustic impedance of the sound waves in the coating. The preset curing reference value is determined based on the coating density and the acoustic characteristics under the curing state. When this value is reached, it can be judged that the evaporation is complete.
[0086] The ultrasonic detector is used to monitor the propagation speed and attenuation characteristics of sound waves in the coating in real time. The acoustic impedance analyzer is used to measure the acoustic impedance of the coating (sound pressure / sound flow rate ratio), reflect the solvent volatilization state, realize non-destructive detection of the solvent content inside the coating, and accurately determine whether the slow-evaporating plasticizer has completely evaporated, thereby ensuring the physical properties and uniformity of the coating.
[0087] During the evaporation process of the slow-evaporating plasticizer, the optical transmittance (usually refers to the transmittance in the visible light range) of the coating mixed solution will change. The less the residual amount of the slow-evaporating plasticizer, the higher the optical transmittance of the coating, until it reaches a stable state. The preset transmittance range is set according to the final coating transparency requirements.
[0088] UV-visible spectrophotometer is used to measure the transmittance of coating at a specific wavelength and monitor the transmittance change until it reaches a stable value. Online optical transmittance monitor is used to realize real-time transmittance detection on the production line, quickly determine the solvent volatilization state, ensure the transparency of the coating meets the display requirements of high-resolution touch screen, and avoid the degradation of optical performance caused by solvent residue, such as fogging, scattering and other problems.
[0089] The coating thickness gradually decreases during the evaporation of the slow-evaporating plasticizer until it reaches a stable value. When the solvent evaporates, the volume of the coating shrinks, causing its thickness to decrease. When the thickness variation is stable within the preset range, it indicates that the slow-evaporating plasticizer has completely evaporated and the coating structure is stable.
[0090] Non-contact optical thickness gauges use laser or white light interferometry technology to monitor coating thickness in real time. Ultrasonic thickness gauges use the time difference of ultrasonic reflection to measure the real-time thickness of the coating. Ellipsometers accurately measure the thickness of thin films by analyzing the polarization changes of light reflection. Ensure the uniformity and consistency of coating thickness and avoid optical performance problems caused by thickness deviation. Achieve precise control of coating thickness and provide ideal initial conditions for subsequent light curing.
[0091] The above-mentioned preset curing reference value, preset light transmittance range, and preset thickness range can be obtained by repeated tests, and a large number of test experiments with the same steps and formulas are performed to summarize the corresponding judgment values.
[0092] The specific structures and usage methods of all the equipment or devices in the above application content, such as the stirring reactor, spraying device, sensor unit, detection equipment, etc., are known to those skilled in the art and will not be repeated here.
[0093] The invention provides an anti-fingerprint coating for a touch screen, which is prepared by a synthesis method of the anti-fingerprint coating for a touch screen.
[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for synthesizing an anti-fingerprint coating for a touch screen, characterized in that the steps include: S1. Mixing a fluorinated copolymer, a reversible crosslinking agent and a multi-component solvent to obtain a coating mixed solution, wherein the multi-component solvent includes a fast-evaporating plasticizer, a slow-evaporating plasticizer and a polar solvent; S2, coating the coating mixed solution on the touch screen, heating after coating to evaporate the fast-volatile plasticizer, and introducing water vapor after evaporation; S3, after stopping the introduction of water vapor, the temperature is raised again to evaporate the slow-evaporating plasticizer, and after the evaporation is completed, light curing is performed to obtain an anti-fingerprint coating for a touch screen.
2. The method for synthesizing the anti-fingerprint coating for touch screen according to claim 1, characterized in that: The step S1 comprises: S1.1, placing the fluorinated copolymer and the reversible crosslinking agent in a stirring reaction vessel, stirring at a speed of 100-200 rpm, a stirring temperature of 30-35°C, and an ambient humidity of 8-10%; S1.
2. Add fast-evaporating plasticizer, increase the stirring speed to 200-300 rpm, reduce the ambient pressure to 0.9-0.95 atm, and continue stirring for 3-5 minutes after the addition is completed; S1.
3. Add slow-evaporating plasticizer, reduce the stirring speed to 100-150 rpm, increase the stirring speed to 150-200 rpm after the addition is complete, add polar solvent, continue stirring for 10-15 minutes after the addition is complete, and obtain a coating mixed solution.
3. The method for synthesizing the anti-fingerprint coating for touch screen according to claim 1 or 2, characterized in that: In the multi-component solvent, calculated by weight percentage, the slow-evaporating plasticizer accounts for 30-50%, the polar solvent accounts for 10-20%, and the balance is the fast-evaporating plasticizer.
4. The method for synthesizing the anti-fingerprint coating for touch screen according to claim 1, characterized in that: The step S2 comprises: S2.
1. Place the touch screen in a spraying station of a spraying device, and then spray the coating mixed solution on the touch screen, wherein the spraying device is provided with a nozzle, a circulating fan, a heating unit and a sensor unit, the atomization frequency of the nozzle is 100-200 kHz, and the spraying time is 1-2 min; S2.
2. After spraying, the coating is heated to 50-60°C. A circulating fan is turned on to blow the coating mixed solution on the touch screen at a horizontal airflow speed of 0.5-1 m / s. When the evaporation of the fast-volatile plasticizer is detected, water vapor is introduced for 3-5 minutes to raise the ambient humidity to 25-30%.
5. The method for synthesizing the anti-fingerprint coating for touch screen according to claim 4, characterized in that: The step of detecting that the evaporation of the fast-volatile plasticizer is complete includes: detecting that the viscosity of the coating mixed solution reaches a preset viscosity value, detecting that the mass of the coating mixed solution decreases to a preset mass range, and detecting that a characteristic absorption peak in the spectrum of the coating mixed solution decreases to at least one of a preset threshold value.
6. The method for synthesizing the anti-fingerprint coating for touch screen according to claim 4, characterized in that: The step S3 comprises: S3.
1. Stop introducing water vapor and adjust the horizontal airflow speed to 0.2~0.5m / s until the ambient humidity reaches 15~20%; S3.2, raising the heating temperature to 90-100° C. for 5-10 min, detecting that the slow-evaporating plasticizer has been evaporated, irradiating the coating mixed solution with ultraviolet light to obtain an anti-fingerprint coating for a touch screen.
7. The method for synthesizing the anti-fingerprint coating for touch screen according to claim 6, characterized in that: The step of detecting that the evaporation of the slow-volatile plasticizer is completed includes: detecting that the acoustic parameter of the coating mixed solution reaches a preset curing reference value, detecting that the optical transmittance change amplitude of the coating mixed solution reaches a preset light transmittance amplitude range, and detecting that the thickness change amplitude of the coating mixed solution reaches at least one of a preset thickness amplitude range.
8. An anti-fingerprint coating for a touch screen, characterized in that: The anti-fingerprint coating for a touch screen is prepared by the synthesis method of the anti-fingerprint coating for a touch screen according to any one of claims 1 to 7, wherein the anti-fingerprint coating for a touch screen comprises a fluorine-containing copolymer, a reversible cross-linking agent and a multi-component solvent, wherein the fluorine-containing copolymer comprises at least one of polytetrafluoroethylene, polyvinylidene fluoride and fluorinated ethylene propylene copolymer, the reversible cross-linking agent comprises at least one of bismaleimide-fulvene dimer, bisthioethyl ether and adipaldehyde, the multi-component solvent comprises a fast-evaporating plasticizer, a slow-evaporating plasticizer and a polar solvent, the fast-evaporating plasticizer comprises at least one of acetone, ethyl acetate and methyl ethyl ketone, the slow-evaporating plasticizer comprises at least one of butyl butyrate, dipropylene glycol methyl ether and cyclohexanone, and the polar solvent comprises at least one of ethanol, methanol and propylene glycol.